Problem-Based Jobsheets for PLC Practicum with a Pick and Place Trainer Kit and FPWIN Pro 7 - Elfitra Rahma Fionandes; Zulwisli; Ilmiyati Rahmy Jasril; Winda Agustiarmi (Journal of Hypermedia & Technology-Enhanced Learning, 2026)
Vocational secondary schools require instructional materials that connect programmable logic controller (PLC) concepts with safe, repeatable practice on industrial automation equipment. This study developed and evaluated a problem-based learning (PBL) jobsheet module for a Panasonic PLC-based Pick and Place Trainer Kit programmed with FPWIN Pro 7. The study used the Define, Design, and Develop stages of the Four-D (4D) model. Five jobsheets were appraised by one subject-matter expert and one instructional-media expert and were then trialled by one vocational teacher and ten Grade XI Industrial Automation students at SMK Pembangunan Teknologi Robotik UNP, Padang, Indonesia. Content and media validity scores were 89.58% and 93.75%, respectively, yielding a composite validity score of 91.67% (Very Valid). Post-use practicality scores were 93.8% from the teacher and 95.0% from students; the participant-weighted post-use mean was 94.9% (Very Practical). Open-ended responses highlighted the usefulness of annotated FPWIN Pro 7 screenshots, problem scenarios, and safety guidance, while also identifying a need for colour-coded wiring diagrams. These findings provide preliminary evidence that the module is valid and usable in this local setting. Because the study did not assess learning effectiveness or include a comparison group, further multi-site and outcome-based evaluation is required.